(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Digital technology provides various significant benefits in the world of education, especially in improving teacher professionalism in the digital era. This study aims to examine the use of technology in the world of education and the challenges faced by teachers in adopting it. The research method used is a literature study by analyzing various relevant literature. The results of the study show that digital literacy, ongoing training, and the use of online learning platforms are the main factors in improving teacher professionalism. However, there are several challenges, such as limited access to technology, minimal training, and resistance to change. Therefore, support is needed from the government and educational institutions in providing adequate infrastructure and policies that encourage innovation in learning